Channeling Midsommar from Celtic Rituals to Pagan Culture and Humanist Criticism - Maharanny Poetri; Cahyani Fitri Melania (Universitas Muhammadiyah Malang, 2024)
Midsommar presents pagan tradition by hosting a midsummer festival by the cult Hårga in Halsingland, Northern Europe. The midsummer festival is a representation of Celtic ritual –consisting of several rituals as a pagan tradition preserved by the Hårga cult. This research aims to identify the representation of Celtic rituals in Ari Aster's Midsommar using Stuart Hall's perspective. Hall (1997) explained that representation is born from the production of the concept of meaning in the mind through language. The representation of Celtic rituals in Midsommar is a form of Hårga’s pagan tradition that among others provokes humanist criticism. This research uses a qualitative method with a cinematography approach. The research data was collected from direct observation of dialogue, narrative, and scenes in the film Midsommar –and presented in the form of selected screenshots. The results of this research include: 1) Midsummer festival is a representation of Celtic ritual. It symbolizes the gratitude of the Hårga cult. 2) Midsummer festival contains ritual instruments that convey the essence of Hårga’s pagan tradition and raise humanist issues. It negates humanity in some of its rituals, thus provoking humanist criticism as a rejection of the Celtic rituals represented. Midsommar menceritakan tradisi pagan festival musim panas oleh kultus Hårga di desa Halsingland, Eropa Utara. Festival musim panas dalam adalah representasi ritual Kelt -terdiri dari beberapa ritual sebagai tradisi pagan yang dilestarikan kultus Hårga. Penelitian ini bertujuan untuk mengidentifikasikan representasi ritual Kelt dalam film Midsommar karya Ari Aster menggunakan perspektif Stuart Hall. Hall (1997) menjelaskan bahwa representasi lahir dari produksi konsep makna dalam pikiran melalui bahasa. Representasi ritual Kelt dalam Midsommar merupakan bentuk tradisi pagan kultus Hårga yang diantaranya mengundang kritik humanis. Penelitian ini menggunakan metode kualitatif dengan pendekatan sinematografi. Data penelitian dikumpulkan dari pengamatan dialog, narasi, dan adegan secara langsung dalam film Midsommar -dan disajikan dalam bentuk gambar tangkapan layar terpilih. Hasil penelitian ini meliputi: 1) Festival musim panas adalah representasi ritual Kelt. Festival musim panas dalam Midsommar melambangkan rasa syukur dari kultus Hårga. 2) Festival musim panas mengandung instrumen ritual yang menyampaikan tradisi pagan kultus Hårga serta menimbulkan isu humanis. Festival musim panas dalam Midsommar menihilkan kemanusiaan dalam beberapa ritualnya sehingga mengundang kritik humanis sebagai penolakkan terhadap ritual Kelt yang direpresentasikan.